A survey on relationships between thyroid hormone levels and clinical findings in dairy calf diarrhea (Veterinary Science Development, 2015)
Calf diarrhea is an important disease that occurs in association with the interaction of various infectious agents and calf susceptibility. The economic losses is associated with death loss and treatment costs, reduction of live weight gain, and reduction of productive life span, which may be considerable. Thyroid hormones previously thought mainly in thermoregulation and energy metabolism. Recently, several studies have challenged on their roles in the metabolic response of animals to certain conditions such as nutritional, environmental, or disease state. The aim of the present study was to survey relationships between thyroid hormones in calves with diarrhea in the different clinical features. Holstein calves (50) within 1 day to 2 months old with signs of diarrhea and healthy calves (40) with similar age and sex were selected. Standard clinical examinations and also dehydration degree assessment were carried out on each calf and recorded accordingly. Calves with clinical signs of diarrhea were divided in different groups based on the severity of the clinical findings, fever and degree of dehydration. Blood samples were taken from the jugular vein from all calves into vacutainer tubes for serum collection.T4, fT4, T3 and fT3 concentrations were measured by validated methods. A significant increase in T4, T3 and fT3 in diarrheic calves was observed (P